Uncovering the Risks: Investigating the Impact of Abnormal 50 g Results of Two-Step Gestational Diabetes Mellitus Screening in Pregnant Women - Sakine Rahımlı Ocakoglu; Bayram Ali Dorum; Zeliha Atak; Özlem Özgün Uyanıklar; Gökhan Ocakoğlu (Genel Tıp Dergisi)

(untitled)
Background/Aims: Gestational Diabetes Mellitus (GDM) is a prevalent medical concern among pregnant women. Timely identification and management of GDM can mitigate the potential for maternal and fetal complications. The present study aimed to explore the maternal characteristics that may result in an isolated elevation in the 50 g Glucose Challenge Test (GCT) results (Pre-GDM condition) and to assess the impact of Pre-GDM status on fetal and neonatal outcomes. Methods: This retrospective trial included 177 pregnant women and 177 infants. All pregnant women who applied to the antenatal clinic were screened for GDM. Patients were divided into two groups: patients with abnormal GCT (50 g levels) but normal 100 g-OGTT results (study or Pre-GDM group) and those with normal 50 g results (control group).Results: The advanced maternal age (AMA) rate was higher in the study group. (14.80% vs. 4.80%, p=0.028). There was a difference between the groups in maternal weight measurements at the first pregnancy visit. The rate of overweighted patients (more than 80 kg at the first pregnancy visit) was higher in the Pre-GDM group (35.20% vs. 5.80%, p<0.001). The rate of fetal macrosomia was higher in the Pre-GDM group (10.20% vs. 0, p<0.05). It was determined that the neonate's head circumference (HC) was larger in the Pre-GDM group (35.15 vs. 34.69, p=0.029) Emergent (primary) cesarean section (C/S) rate with cephalopelvic disproportion (CPD) indication was higher in the fetal macrosomia group (p<0.05). The power of the current study was determined as 87%Conclusions : According to study result the patients in the Pre-GDM group is at risk of fetal macrosomia, which increases the risk of C/S. In overweighted and patients over 35 years old, 75 g OGTT may be more sensitive in detecting glucose metabolism disorders.